Multimodal fluorescence microscopy of prion strain specific PrP deposits stained by thiophene-based amyloid ligands - Magnusson, Karin (Prion, 2014)
The disease-associated prion protein (PrP) forms aggregates which vary in structural conformation yet share an identical primary sequence. These variations in PrP conformation are believed to manifest in prion strains exhibiting distinctly different periods of disease incubation as well as regionally specific aggregate deposition within the brain. The anionic luminescent conjugated polythiophene (LCP), polythiophene acetic acid (PTAA) has previously been used to distinguish PrP deposits associated with distinct mouse adapted strains via distinct fluorescence emission profiles from the dye. Here, we employed PTAA and 3 structurally related chemically defined luminescent conjugated oligothiophenes (LCOs) to stain brain tissue sections from mice inoculated with 2 distinct prion strains. Our results showed that in addition to emission spectra, excitation, and fluorescence lifetime imaging microscopy (FLIM) can fruitfully be assessed for optical distinction of PrP deposits associated with distinct prion strains. Our findings support the theory that alterations in LCP/LCO fluorescence are due to distinct conformational restriction of the thiophene backbone upon interaction with PrP aggregates associated with distinct prion strains. We foresee that LCP and LCO staining in combination with multimodal fluorescence microscopy might aid in detecting structural differences among discrete protein aggregates and in linking protein conformational features with disease phenotypes for a variety of neurodegenerative proteinopathies.